SISTEM PENGATURAN BEBAN GENERATOR TIGA FASA SECARA OTOMATIS BERBASIS INTERNALLY TRIGGERED TRIAC - Muhammad Deval Efendi; Abdul Muis Prasetia; Linda Sartika (Elektrika Borneo, 2022)
A generator is an electrical machine that converts mechanical/motion energi into electrical energi. The performance of the generator is strongly influenced by the load, so when the load exceeds the generator limit, it is called overload disturbance. In this study, the author makes a generator load regulation sistem based on Internally Triggered TRIAC which functions to reduce the voltage value to the load automatically so that the current value can always be at the set point, which is 0.50 A. In this study, a resistive load in the form of an incandescent lamp with specifications of 100 W is used. As many as two and one 5 W incandescent lamp. For one 100 W incandescent lamp, the current value is 0.40 A and for one 5 W incandescent lamp, the current value is 0.06 A. When all loads are on, the current value ready by the sensor is 0.86 A so that the sistem responds to a load. More because the current value exceeds the set point. The sistem lowers the voltage value to 17.67 V so that the current value can always be at the set point of 0.50 A.